Spatiotemporal Variability of Extreme Precipitation and Influence of Climate Factors and Topography in the Dongting Lake Basin, Southern China - Yuannan Long; Chunfu Huang; Changbo Jiang; Zhiyong Huang; Xinkui Wang; Shixiong Yan (International Journal of Climatology, 2025)
The intensification of global climate change and regional human activities has led to an increase in the frequency and intensity of extreme precipitation, posing significant challenges to regional sustainable development. Using daily precipitation observation data from 108 meteorological stations during 1960–2020, the spatiotemporal distribution characteristics of extreme precipitation in the Dongting Lake Basin (DLB) are revealed, and the mechanisms driving extreme precipitation variation in the DLB are investigated. The results showed that with the increase in the frequency, intensity and amount of extreme precipitation, the DLB is trending towards increased humidity. However, consecutive wet days have declined significantly at a rate of −0.015 days/year, indicating that more short‐duration but high‐intensity extreme precipitation are likely to occur in the future. These changes have intensified with the increase in regional average warming. In contrast, the weakening of the East Asian Summer Monsoon (EASM) amplifies changes in extreme precipitation through nonlinear enhancement mechanisms, particularly when interacting with other climate drivers. Additionally, extreme precipitation exhibits a sensitive response to elevation. Specifically, low‐altitude areas tend to experience more frequent and intense extreme events, whereas high‐altitude regions are more prone to short‐duration heavy rainfall. The fastest growth in extreme precipitation was observed in the hilly‐valley transition zone between the northern Xuefeng Mountains and southern Wuling Mountains. At the sub‐basin level, the Lishui River Basin exhibits relatively minor variations in most extreme precipitation indices, while the Xiangjiang River Basin records the greatest increase in the frequency of extreme precipitation. These patterns may be explained by differences in the categories of dominant climate drivers and the strength of their associated impacts.